2004
DOI: 10.1089/0892779041271661
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiofrequency Ablation, Cryoablation, and Nephrectomy in Treating Implanted VX-2 Carcinoma in Rabbit Kidneys

Abstract: Radiofrequency ablation, cryoablation, and radical nephrectomy were all efficacious in the treatment of implanted VX-2 renal tumors compared with untreated controls (P = 0.002). No statistically significant difference was found between any of the three treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There was no significant difference between the results of RFA, cryoablation and nephrectomy in small rabbit kidney tumors of less than 1 cm. All these treatment modalities were efficient 27 . Moreover, there was no impact of RFA on renal function and blood pressure after ablation of small tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the results of RFA, cryoablation and nephrectomy in small rabbit kidney tumors of less than 1 cm. All these treatment modalities were efficient 27 . Moreover, there was no impact of RFA on renal function and blood pressure after ablation of small tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of focused transducers is the short duration of treatment (less than 10 s, which may be further reduced by optimization), making this thermal modality competitive with cryoablation and radiofrequency ablation [42][43][44]. Furthermore, this non-invasive and short-term treatment with dual-mode technology can be clinically applied to skin rejuvenation and tightening via heating of tissue to 65-70 • C, which causes collagen contraction, denaturation, and initiation of collagen synthesis [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using an animal model [13] , it was suggested that RFA gave a higher cure rate and a lower rate of metastatic disease in the kidney cancer management. This outcome could be the result of the combination of tumour destruction and coagulation of perirenal fat during RFA [13] .…”
Section: Discussionmentioning
confidence: 99%
“…This outcome could be the result of the combination of tumour destruction and coagulation of perirenal fat during RFA [13] . This might suggest that our method of ablation may give a better chance of reduced tumour recurrence than the standard PN.…”
Section: Discussionmentioning
confidence: 99%